(untitled) (Altre Modernità, 2022)
In March 2020, more than 100 governments around the world imposed partial or full lockdown policies prohibiting people to leave their homes except for activities deemed essential (e.g. procuring food, going to work) to reduce SARS-CoV-2 transmissions. Furthermore, authorities, media and peers encouraged people to adopt physical distancing behaviors, requesting not to touch each other and even keep a distance of at least one to two meters from one another. Cultural and literary productions—so-called Corona Fictions—represent and process the multitude of ways the population perceived and coped with the lockdown situation during the pandemic and its diverse effects. While literary texts written during confinement and published in anthologies focus on emotional states enhanced by the psychological impact of the lockdown, the narratives in films such as Norberto Ramos del Val’s ¡Ni te me acerques! (2020) focus on negotiating the process of physical distancing itself. This contribution will, thus, look at the representations of physical distancing in written and audiovisual productions from the first lockdown and analyze the similarities therein. From a cultural studies point of view, we are particularly interested in the ways these Corona Fictions negotiate physical distancing, isolation and self-reflection in their narratives of the respective medium.